The Afterlife in African Traditional Religion: Notions of Punishment and Immortality - Lougheed, Kirk (Journal for the academic study of religion, 2025)
This article explores the nature of the afterlife in African Traditional Religion. According to this belief, when a person dies, their spirit transitions to become a member of the living dead for about five generations after which they become a nameless ghost and their personal identity is lost. After explaining these ideas in more detail, I turn to a philosophical examination of the afterlife by focusing on two concepts in punishment and immortality. With respect to the former, African Traditional Religion says that justice is doled out in an individual's earthly life, not in the afterlife. With respect to the latter, African Traditional Religion's account of the afterlife provides life extension but ultimately still ends in non-existence. I assess some of the philosophical upshots and downsides of these positions before concluding that much philosophical work remains to be done in exploring these concepts in their own right, in addition to examining where cross-cultural investigations might lead.